Patients’ experiences of Submucous Resection operation under local anaesthesia with deep sedation - Paul, Mitun Kumar; Islam, Baishakhi (Mediscope, 2022)
Background: Submucous resection (SMR) operation can be done under local or general anaesthesia. SMR under local anaesthesia with deep sedation is a safe, simple, cost-effective and reliable procedure for patients in developing countries like Bangladesh. Objective: To observe the experiences of patients regarding SMR under local anaesthesia (L/A) with deep sedation. Methods: After taking proper approval from Institutional Review Board, fifty (50) cases were selected for doing SMR operation which was done with maintaining all aseptic precautions in Mymensingh Medical College Hospital from July 2013 to July 2014. Assessment of effectiveness under LA was done after completion of SMR. Results: In our study, there were 26 (52%) male and 24 (48%) female patients. Majority of the patients (70%) belonged to the age range of 18-37 years. 32 patients (64%) felt the procedure to be completely painless (Grade 1), and 16 patients (32%) complained of slight discomfort (Grade 2). None of the patients experienced moderate or severe discomfort. Conclusion: SMR operation under L/A with deep sedation is very simple, safe, cost effective, less time consuming and highly acceptable procedure to the patient and the surgeon. Mediscope 2022;9(1): 16-19